2016
DOI: 10.1007/s12526-016-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

The amphipod assemblages of Sabellaria alveolata reefs from the NW coast of Portugal: An account of the present knowledge, new records, and some biogeographic considerations

Abstract: Amphipod assemblages associated with the biogenic reefs built by the honeycomb worm Sabellaria alveolata were studied at two sites (Praia da Aguda and Belinho) along the northwestern coast of Portugal. A total of 3909 specimens were collected, comprising 14 different amphipod species. A first record from the northeastern Atlantic coast was registered here for the species Caprella santosrosai, which was, up to now, recorded only along the Mediterranean coast of the Iberian Peninsula. A male specimen collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Similarities are more marked between the Western Basin (Northern and Southern areas) and the North-Eastern Atlantic European coasts, the latter having slightly less similarities with the Eastern Basin (Figure 4). A biogeographic affinity between the Mediterranean and the eastern Atlantic regions has been observed also for other peracarids, amphipods [11,84], and other invertebrate groups: ascidians [85], anthozoans [86], and opisthobranch molluscs [87]. In their study of the assemblage patterns of amphipods associated with the macroalgae Corallina elongata along the north-south and Atlantic-Mediterranean axes across the Strait of Gibraltar, Guerra-Garca et al [11] found that 64% of species have an Atlantic-Mediterranean distribution; these authors considered the Mediterranean-Atlantic axis to be a relatively homogeneous zone, i.e., without a distinct change in the distribution pattern of peracarid assemblages.…”
Section: General Pattern Of the Peracarida Faunamentioning
confidence: 67%
“…Similarities are more marked between the Western Basin (Northern and Southern areas) and the North-Eastern Atlantic European coasts, the latter having slightly less similarities with the Eastern Basin (Figure 4). A biogeographic affinity between the Mediterranean and the eastern Atlantic regions has been observed also for other peracarids, amphipods [11,84], and other invertebrate groups: ascidians [85], anthozoans [86], and opisthobranch molluscs [87]. In their study of the assemblage patterns of amphipods associated with the macroalgae Corallina elongata along the north-south and Atlantic-Mediterranean axes across the Strait of Gibraltar, Guerra-Garca et al [11] found that 64% of species have an Atlantic-Mediterranean distribution; these authors considered the Mediterranean-Atlantic axis to be a relatively homogeneous zone, i.e., without a distinct change in the distribution pattern of peracarid assemblages.…”
Section: General Pattern Of the Peracarida Faunamentioning
confidence: 67%
“…They are easy to capture, have a short generation turnover and are cosmopolitan species. The order Amphipoda is dominant in temperate coastal environments; most species are highly specific for a single habitat and display limited dispersal, thus exhibiting a strong genetic cohesion and taxonomic homogeneity [10,11,[36][37][38], which provide spotted information on a regional spatial scale. Further, at the taxonomic level of genus, they are commonly found worldwide and analyses from different localities can be comparable as the co-generic species are ecological equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…Due the high connectivity between eastern Atlantic and Mediterranean area, which has already caused a high similarity in the Portuguese and Mediterranean amphipod fauna (Plicanti et al 2016) it can be supposed that the Atlantic Ptilohyale littoralis may have spread into the Mediterranean, or vice versa, Parhyale plumicornis into the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%